COMMUNICATION STRATEGIES USED BY TOURIST GUIDES AT BENANG STOKEL CENTRAL LOMBOK - Jumadil, Jumadil; Siswana, Siswana (LPPM Institut Pendidikan Nusantara Global, 2023)
This study deals with the communication strategies used by tourist guides at Benang stokel, Central Lombok, West Nusa Tenggara Province. It was aimed to investigate types of communication strategies. This study was conducted by applying a qualitative research design. The sources of the data were selected from two tourist guides in Benang stokel. The instrument applied in this study were observation sheet, filed notes, and interview. Data were analyzed using descriptive analysis technique, by describing types of communication strategies and the process communication strategies used by tourist guides at Benang stokel, Central Lombok, West Nusa Tenggara Province. Based on the analysis of data, it was found that the process of communication strategies used by tourist guide occur during the communication with foreign tourist is dominantly achievement or compensatory strategies, self-monitoring strategies, and interactional strategies. In the conversation, they did not always go as smoothly as we think. In fact, communication strategies had been applied by tourist guides even though they did not know about the theory behind it.